Laparoscopic extraction of gastric self-expandable metallic stent after migration in ileum: A case report. (2018) - Terryn, F.-X.; Dereeper, E.; Lo Bue, S.
Highlights: Revisional surgery in bariatric patients can sometimes lead to life-threatening complications. A good combination between endoscopic procedure and surgery is needed to treat a gastric perforation. Self-expandable stents have a high migration rate, and a laparoscopic extraction is feasible. Abstract: Revisional surgery in bariatric patients can sometimes lead to life-threatening complications that need a fast diagnosis and treatment as well as a multidisciplinary approach. If left undiagnosed or untreated, this may lead to sepsis, multiple organ failure, and death. In this case report, we describe the management of a gastric perforation which occurred after conversion of a gastric banding to a sleeve gastrectomy.